Unprotected left main revascularization: Percutaneous coronary intervention versus coronary artery bypass. An updated systematic review and meta-analysis of randomised controlled trials. - Luca Testa; Azeem Latib; Mario Bollati; Rocco Antonio Montone; Antonio Colombo; Filippo Crea; Francesco Bedogni (PLoS ONE)
Background The optimal treatment of unprotected left main (UPLM) with either PCI or CABG remains uncertain. Aim The purpose of this study was to determine the comparative safety and efficacy of PCI versus CABG in patients with UPLM disease. Methods Search of BioMedCentral, CENTRAL, mRCT, PubMed, major cardiological congresses proceedings and references cross-check (updated November 2016). Outcomes were the rate of MACE [all cause death, MI, stroke], the rates of the individual components of MACE and the rate of target vessel revascularisation (TVR). Results We identified 6 Randomised Controlled Trials totalling 4717 patients allocated to PCI or CABG. At 1 year follow up, PCI and CABG were substantially equivalent with respect to the rates of MACE [PCI 8.5% vs CABG 8.9%, OR 1.02,(0.76-1.36), p = 0.9], death [PCI 5.4% vs CABG 6.6%, OR 0.81,(0.63-1.03),p = 0.08] and MI [PCI 3.4% vs CABG 4.3%, OR 0.80(0.59-1.07), p = 0.14]. Notably, PCI was associated with a significantly lower rate of stroke [PCI 0.6% vs CABG 1.8%, OR 0.36,(0.17-0.79), p = 0.01] and with a significantly higher rate of TVR [PCI 8.7% vs CABG 4.5%, OR 2.00(1.46-2.75), p<0.01]. At a median follow up of 5years, the rates of MACE were similar between the two strategies: PCI 14.6% vs CABG 13.8%, OR 1.02(0.76-1.38), p = 0.89. Likewise, the rates of death [PCI 8% and CABG 7.7%, OR 1(0.77-1.31), P = 0.9], MI [PCI 6.1% vs CABG 5%, OR 1.41(0.85-2.34), P = 0.19, I2 59%], and stroke [PCI 2% vs CABG 2.2%, OR 0.85(0.42-1.81), p = 0.65,] were similar while PCI was associated with a significantly higher rate of TVR [14.5% vs CABG 8.9%, OR 1.73(1.41-2.13), p<0.01]. Conclusion In patients with UPLM disease, PCI and CABG are associated with similar rates of MACE and mortality at 1 year as well as after 5 years. Differences can be detected for individual end points at both short and long term FU.